Metabolic thrift and the genetic basis of human obesity - O’Rourke, Robert W. (2014)
Evolution has molded metabolic thrift within humans, a genetic heritage that, when thrust into our modern “obesogenic” environment, creates the current obesity crisis. Modern genetic analysis has identified genetic and epigenetic contributors to obesity, an understanding of which will guide the development of environmental, pharmacologic, and genetic therapeutic interventions. “The voyage was so long, food and water ran out. One hundred of the paddlers died; forty men remained. The voyagers finally reached Fitinui, then Aotona.” -From “The Story of Aka”, in The Native Culture in the Marquesas by E. S. Craighill Handy